Five centuries of ways to the revival of the Olympics - Bubka S.N (Kharkov National Pedagogical University, 2012)
The article presents an analysis of the revival of the Olympic Games in the countries of Western, Central Europe and North America in the period from XV to XIX centuries. Prerequisites including society humanization, development of education, science and major national systems of physical education, development of competitive sports in different organizational forms and scales, which contributed to the creation of the environment initiating the revival of the Olympics, have been considered. The role of personalities in the revival of the Olympic movement during five centuries of the historical development of the society has been shown.